Analysis and modeling of flicker noise in lateral asymmetric channel MOSFETs. (January 2016) - Agarwal, Harshit; Kushwaha, Pragya; Gupta, Chetan; Khandelwal, Sourabh; Hu, Chenming; Chauhan, Yogesh Singh
Highlights: Flicker noise behavior in presence of lateral asymmetry is studied. Noise model based on Klaassen Prins method underestimates 1/f noise in such devices. New model is developed and the physics behind noise underestimation is discussed. This study also explain 1/f noise degradation observed in real devices. Abstract: In this paper, flicker noise behavior of lateral non-uniformly doped MOSFET is studied using impedance field method. Our study shows that Klaassen Prins (KP) method, which forms the basis of noise model in MOSFETs, underestimates flicker noise in such devices. The same KP method overestimates thermal noise by 2–3 orders of magnitude in similar devices as demonstrated in Roy et al. (2007). This apparent discrepancy between thermal and flicker noise behavior lies in origin of these noises, which leads to opposite trend of local noise power spectral density vs doping. We have modeled the physics behind such behavior, which also explain the trends observed in the measurements (Agarwal et al., 2015).